2011
DOI: 10.1038/aja.2011.46
|View full text |Cite
|
Sign up to set email alerts
|

The ability of sperm selection techniques to remove single- or double-strand DNA damage

Abstract: A wide variety of techniques for the preparation of sperm are currently available, of which the most commonly employed are densitygradient centrifugation (DGC) and swim-up (SUP). To date, these methods appear to be effective in selecting functional sperm for assisted reproduction techniques (ART), but they may have negative effects on sperm DNA. In this study, the ability of these semen processing techniques to eliminate spermatozoa containing single-and double-strand DNA damage was assessed by the two-tailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 39 publications
1
38
1
1
Order By: Relevance
“…While one study showed that the DGC is more effective than SUP in reducing the percentage of sperm with DNA damage [25], another one, in contrast, demonstrated that SUP recovers lower percentage of sperm with fragmented DNA as compared to DGC [37]. Enciso et al [11] showed that SUP and DGC are equally efficient in eliminating spermatozoa containing double-strand DNA damage and sperm with highly damaged DNA, as characterized by the presence of both single-and double-strand DNA breaks. However, DGC was more efficient than SUP in selecting spermatozoa that are free from single-strand DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While one study showed that the DGC is more effective than SUP in reducing the percentage of sperm with DNA damage [25], another one, in contrast, demonstrated that SUP recovers lower percentage of sperm with fragmented DNA as compared to DGC [37]. Enciso et al [11] showed that SUP and DGC are equally efficient in eliminating spermatozoa containing double-strand DNA damage and sperm with highly damaged DNA, as characterized by the presence of both single-and double-strand DNA breaks. However, DGC was more efficient than SUP in selecting spermatozoa that are free from single-strand DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Several semen separation techniques have been developed to separate the sperm fraction for use in assisted reproductive techniques. The most commonly used protocols are density-gradient centrifugation (DGC) and swim-up (SUP) [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, centrifugation swim-up (technique was applied for in vitro sperm activation. Centrifuge swim-up was the most commonly methods used to separate the sperm fraction for use in ARTs [22]. Processing and isolating sperm from the whole semen specimen as highly motile spermatozoa have been tried with variable success before its use for ARTs [23].…”
Section: Discussionmentioning
confidence: 99%
“…Congruent with this idea are those reports claiming that the predictive value of SDF is low when ICSI is used. 14,15,21 It should be noted that while the incidence of SDF in the selected population may in fact decline after sperm selection, there is still a reasonable chance of accidently selecting one of the remaining underlying sub-population of DNA damaged spermatozoa that was not initially excluded in the selection procedure, i.e., a certain level of damaged spermatozoa still remains in the sample, even under the most stringent and rigorous conditions for sperm selection (see data in Zini et al 42 Gosálvez et al 38 and Enciso et al 43 ). By way of an example, if we analyse the data shown by Santiso et al 48 in Figure 1, in some cases and after a swim-up procedure, we are selecting sperm subpopulations containing shorter telomeres than those considered as normal.…”
Section: Sperm Selection and Sperm Dna Damagementioning
confidence: 99%
“…The efficiency for sperm selection and its association with a decrease in SDF is a topic that has been studied from a range of perspectives [42][43][44][45] but deserves further investigation, especially if we take into account possible collateral effects associated with the production of iatrogenic sperm damage via sperm handling. 46 Some studies have reported the benefit of using selected spermatozoa to improve pregnancy 47 and it is logical that the probability of selecting a sperm for ICSI free of DNA damage should increase if density gradient centrifugation or swim-up procedures are implemented.…”
Section: Sperm Selection and Sperm Dna Damagementioning
confidence: 99%